Glamour studies: The state of the field. Issue 1 (1st April 2019) - Gundle, Stephen
This article, by the author of Glamour: A History in 2008, reassesses his own book and discusses the books of three other authors who in the last ten years have published analyses of glamour. Glamour in Six Dimensions in 2009, by Judith Brown, connects glamour to literary modernism, while Carol Dyhouse's book Glamour: Women, History, Feminism (2010) provides a social history of feminine glamour in Britain, mainly between the 1920s and the 1960s. In The Power of Glamour in 2013, Virgina Postrel attempts to theorize glamour as a 'non-verbal rhetoric' centred on dreams of escape and transformation. Postrel's argument is judged to be flawed in part because it lacks the materiality of Brown, the sharp gender focus of Dyhouse and the class-based historical approach of Gundle. It is argued that studies of glamour must start from what has generally been understood by the term. Theoretical advances may be achieved when social theory and material cultural approaches are more systematically brought together.